Analysis Study of Soil Phosphorus Availability on the Growth of Oil Palm Seedlings (Elaeis guineensis Jacq.) with the Application of Liquid Fertilizer and Guano Fertilizer (Bat Manure) in Main-Nursary - Lubis, Fiqi Alfisar; Kusbiantoro, Dedi; Asbur, Yenni; Purwaningrum, Yayuk; Kurniawan, Indra Saputra (Contributions of Central Research Institute for Agriculture, 2024)
Guano fertilizer is a fertilizer derived from bat dung which is organic fertilizer, and contains a lot of P elements that can increase plant growth both vegetatively and generatively. The purpose of this study was to determine the effect of the application of Banana Stem POC and Guano fertilizer (Bat Manure) on soil P availability and growth of oil palm seedlings in the Main-Nursery. The experimental design used was a factorial Randomized Group Design with three replications. The treatments were arranged in four levels each of Banana Stem POC (C0 = Control, C1 = 1.5 ml/l water/Polybeg, C2 = 3 ml/l water/Polybeg, C3 = 4.5 ml/l water/Polybeg) and Guano Fertilizer (K0 = Control, K1 = 200 g/Polybeg, K2 = 400 g/Polybeg, K3 = 600 g/Polybeg). Banana stem is an agricultural waste that can be used as a useful product because it contains potential compounds, while Bat guano fertilizer has several advantages, namely it can stay longer in soil tissue, increase soil productivity and provide food for plants. These results show that the application of Banana Stem POC and Guano Fertilizer can increase the growth of plant height, stem diameter, leaf area and P available.